Mas-related gene (Mrg) C receptors inhibit mechanical allodynia and spinal microglia activation in the early phase of neuropathic pain in rats. (8th April 2016) - Wang, Dongmei; Xue, Yaping; Chen, Yajuan; Ruan, Liqin; Hong, Yanguo
Highlights: Intrathecal (i.t.) administration of BAM8-22 inhibited mechanical allodynia on day 2 post-SNL surgery. I.t. BAM8-22 reversed microglia activation in the spinal dorsal horn. I.t. BAM8-22 suppressed expression of nNOS in the dorsal root ganglion (DRG). L5 SNL reduced the level of MrgC receptor mRNA in the injured L5 DRG, but not the uninjured adjacent L4 or L6 DRG, on day 2 post-SNL. This study suggests that MrgC receptors could be targeted as a novel therapy for neuropathic pain with limited unwanted effects. Abstract: Mas-related gene (Mrg) C receptors are exclusively expressed in the trigeminal and dorsal root ganglia (DRG). However, their functional roles are poorly understood. This study was aimed to determine the effect of MrgC receptors on pain hypersensitivity in the early phase of neuropathic pain and its underlying mechanisms. Intrathecal (i.t.) administration of the selective MrgC receptor agonist bovine adrenal medulla 8–22 (BAM8-22) at 1 or 10 nmol attenuated mechanical allodynia one day after L5 spinal nerve ligation (SNL) surgery. I.t. BAM8-22 (10 nmol) inhibited SNL-induced microglia activation in the spinal dorsal horn on day 2 post-SNL. The BAM8-22 treatment also abolished SNL-induced upregulation of neuronal nitric oxide synthesis (nNOS) in the dorsal root ganglia (DRG). On the other hand, SNL, but not sham, surgery reduced the expression of MrgC receptor mRNA in the injured L5 DRG without changing thier levels in the adjacent uninjured L4 or L6 DRG on day 2 following the surgery. These results suggest that the activation of MrgC receptors can relieve pain hypersensitivity by the inhibition of nNOS increase in DRG neurons and microglia activation in the spinal dorsal horn in the early time following peripheral nerve injury. This study provides evidence that MrgC receptors could be targeted as a novel therapy for neuropathic pain with limited unwanted effects.